2022
DOI: 10.1080/19012276.2022.2074524
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Risk factors and mechanisms of radicalization in lone-actor grievance-fueled violence

Abstract: The purpose of this systematic review is to identify risk factors associated with lone-actor grievance-fueled violence. In this paper, I focus on five violent lone-actor "types"; lone-actor terrorists, workplace attackers, school shooters, rampage shooters and violent Incels. Data synthesis of the 78 included studies led to the identification of nine risk factors: 1) sociodemographic background; 2) social ties; 3) interpersonal rejection; 4) mental illness; 5) subclinical personality traits; 6) strain; 7) grie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 115 publications
1
15
0
Order By: Relevance
“…A recent systematic review of 78 studies identified nine risk factors for lone-wolf attacks, under which they classify violent incels [59]. These nine are (i) sociodemographic characteristics, (ii) social ties, (iii) interpersonal rejection, (iv) mental illness, (v) subclinical personality traits, (vi) strain, (vii) grievances, (viii) emotional traits/states, and (ix) cognitive processes.…”
Section: Why Do Some Incels Commit Violence?mentioning
confidence: 99%
“…A recent systematic review of 78 studies identified nine risk factors for lone-wolf attacks, under which they classify violent incels [59]. These nine are (i) sociodemographic characteristics, (ii) social ties, (iii) interpersonal rejection, (iv) mental illness, (v) subclinical personality traits, (vi) strain, (vii) grievances, (viii) emotional traits/states, and (ix) cognitive processes.…”
Section: Why Do Some Incels Commit Violence?mentioning
confidence: 99%
“…Online radicalization processes have been of major concern, not only in the area of terrorism, but in the wider field of grievance-based violence. In fact, recent work has introduced a comparative approach that builds on the commonalities between perpetrators of, for example, high school shootings, hate crimes, and terrorist attacks ( Brooks and Shaw, 2022 ; Clemmow et al, 2022 ; Ebbrecht, 2022 ). In particular for offenders deemed to be lone actors, the boundaries between terrorism and other forms of offending are blurred ( Capellan, 2015 ; Kenyon et al, 2021a ; Clemmow et al, 2022 ).…”
Section: Online Radicalization As a Cause For Common Concernmentioning
confidence: 99%
“…LAGFV serves as an umbrella term to conceptualize this broad cohort of offending, with grievance and/or fixation considered universal contributors to lone actor violence. Although this terminology could also be represented as Lone Actor Grievance and Fixated Fueled Violence (LAGFFV), for the purpose of consistency with prior research ( Pathé et al, 2018 ; Barry-Walsh et al, 2020 ; Brooks and Shaw, 2022 ; Clemmow et al, 2022 ; Ebbrecht, 2022 ), the present review will refer to this offending as LAGFV which is considered to encompass the role of fixation. LAGFV at this juncture is a blurry construct without definitive rules and boundaries, and instead provides a guiding conceptualization of a diverse group of offenders who commit targeted violence towards others.…”
Section: Introductionmentioning
confidence: 99%